Digital Payment Systems and Gen Z E-Commerce Purchasing Behavior: Evidence from Shopee Users - Natashah Dewanti; Muhammad Rafly; Nazihah Nur Ilmiyah; Maya Panorama (Al Dzahab, 2026)
Purpose: This study aims to examine Gen Z students’ purchasing behavior on the Shopee e-commerce platform, focusing on purchase frequency, preferred product categories, and the role of digital payment systems in influencing purchasing decisions. Design/Methodology/Approach: This research employed a quantitative descriptive approach using primary data collected through questionnaires. The sample consisted of 55 students from the Faculty of Islamic Economics and Business (FEBI) at UIN Raden Fatah Palembang who actively use Shopee. Respondents were selected using purposive sampling, while secondary data were obtained from relevant literature and previous studies. Findings: The results indicate that most students shop on Shopee approximately 1–3 times per month, with fashion products being the most frequently purchased category. Purchasing decisions are primarily influenced by competitive prices and promotional discounts. In addition, the convenience and accessibility of digital payment systems, particularly ShopeePay, further encourage online purchasing behavior among Gen Z students. Research Implications: These findings highlight the importance for e-commerce platforms to develop effective marketing strategies that combine competitive pricing, attractive promotional campaigns, and convenient digital payment services in order to maintain consumer engagement, especially among Gen Z as a key market segment.